2018
DOI: 10.3390/su10030653
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Fragmented Last Mile Deliveries to Nanostores by Utilizing Spare Transportation Capacity—A Simulation Study

Abstract: Last mile deliveries in urban areas cause a disproportionate unsustainable impact, while it is also the most expensive part of the supply chain. This is particularly true for freight flows that are characterized by fragmentation. Logistically, this becomes apparent in vehicles that are driving around with a low vehicle fill rate, leading to the unnecessary presence of freight vehicles in our cities. This study focuses on the operational feasibility of utilizing the spare transportation capacity of a service-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 40 publications
0
26
0
3
Order By: Relevance
“…The investigation of Kin et al [21] allowed to improve the management of the use of the space of the cargo trucks, to reduce the unnecessary movements during the supply of urban zones in Belgium. The synchronization model for Belgian inland transport (SYMBIT) is a model based on agents simulating grouping scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The investigation of Kin et al [21] allowed to improve the management of the use of the space of the cargo trucks, to reduce the unnecessary movements during the supply of urban zones in Belgium. The synchronization model for Belgian inland transport (SYMBIT) is a model based on agents simulating grouping scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Last mile Brown and Guiffrida [34], Kin, et al [30], Rizet, et al [35] Discussing e-commerce Handling last-mile delivery Transport in the last mile is not used to its full capacity…”
Section: Logistics Systemmentioning
confidence: 99%
“…One area of potential improvements for environmental-friendly purchasing of transport services [31], reverse logistics [32], transport during the last mile [30] and, in particular, consumer transport [10,29,33,34], and other suppliers in the network [15,22]. Browne, et al [10], who assessed the energy consumption of different product supply chains, found that the energy consumption that was used to transport goods during the last mile to the point of consumption was greater than that of all of the upstream transport activities combined.…”
Section: Introductionmentioning
confidence: 99%
“…Several urban freight transport strategies could be adopted to find a good balance between positive impacts on accessibility and economic development and negative externalities in terms of congestion and polluting emissions (e.g., [2,3]). Recent and relevant solutions refer to: Demand management (e.g., [4,5]); electrification (e.g., [6,7]), regulatory measures (e.g., [8,9]) and improved capacity utilization (e.g., [10,11]).…”
Section: Introductionmentioning
confidence: 99%